PENGGUNAAN MEDIA BERGAMBAR MAJALAH PINTAR (MAPIN) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS 2 SDN KARANGANYAR II PAITON - Maulitha Yuraida Rachman; Didit Yulian Kasdriyanto; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted because of the low reading ability of students, students tend to be less enthusiastic, get bored quickly, and are less interested in reading, Lack of use of interesting media during the ongoing learning process. This study aims to improve the reading ability of grade 2 students of SDN Karanganyar II Paiton in the Indonesian language subject on the use of capital letters using illustrated media in the form of Smart Magazine.The research method used is classroom action research. The subjects of the study were students in grade 2 of SDN Karanganyar II totaling 11 students. The study was conducted in 2 cycles, in each cycle there were 2 meetings in classroom action research there were 4 stages (planning, activities, observation, and reflection) throughout the process of the two cycles. By collecting data through instruments in the form of tests used to test competency achievement or conduct assessments. This study was conducted with 2 cycles starting from February 10, 2025 to February 18, 2025.The results showed that students' reading ability always increased. In the first cycle stage, the percentage of students' reading ability reached 45.45% with 5 students completing the course. In cycle II, students' reading ability increased to 90.90% with the number of students who completed reaching 10 students. The increase in reading ability occurred because the researcher used learning media in the form of Smart Magazine.